Memory consolidation reconfigures neural pathways involved in the suppression of emotional memories - Yunzhe Liu (Nature Portfolio, 2016)
As memories consolidate over time, they become resistant to change, though how this impacts the volitional suppression of memories is not known. Liu and colleagues show that, after overnight consolidation, aversive memories exhibit distributed prefrontal representations and are harder to suppress.